Performance and muscle activity during a high-intensity intermittent task after the ingestion of sodium bicarbonate: A randomized, double-blind, placebo-controlled, crossover study - Kalytczak, M. M.; Battazza, R. A.; Baker, J. S.; Biasotto-Gonzalez , D. A.; Kalytczak, J. D.; Leite, G. dos S.; Bocalini, D. S.; Politti, F. (Journal of Human Sport & Exercise, 2023)
The aim of the present study was to determine whether the ingestion of sodium bicarbonate (NaHCO3) promotes changes in strength, muscle activity, and perceived exertion in trained individuals following high-intensity intermittent exercise. Twelve trained men were enrolled in a randomized, double-blind, crossover study. Each participant underwent two interventions with a 14-day washout period: i) alkalosis (ALK) - administration of gelatinous capsules containing 0.3 g.kg-1 of NaHCO3; ii) placebo (PLA) - administration of capsules containing 0.3 g.kg-1 of calcium carbonate (CaCO3). The outcomes (electromyographic activity of the quadriceps, peak torque, pH, lactate, scales of perceived effort and pain) were collected during a dynamic high-intensity intermittent protocol performed on an isokinetic dynamometer. Repeated-measures ANOVA revealed no differences between conditions for any of the outcomes analysed. Based on the present findings, the ingestion of sodium bicarbonate does not promote changes in muscle activity, strength of the quadriceps, or perceptions of effort and pain in trained individuals during high-intensity intermittent exercise on an isokinetic dynamometer.